Ralph Johnson Bunche : public intellectual and Nobel Peace laureate - Lindsay, Beverly (Urbana : University of Illinois Press, 2007)
"Nobel Peace Prize-winner Ralph Johnson Bunche (1904-71) was one of the twentieth century's foremost diplomats and intellectuals. In the wake of centennial celebrations of his birth, leading scholars and diplomats assess Bunche's historical importance and enduring impact on higher education, public policy, and international politics. Their essays reveal not only the breadth of Bunche's influence, such as his United Nations work to broker peace during times of civil war in Africa, the Middle East, and Asia, but also the depth of his intellectual perspectives on race, civil rights, higher education, and international law. Probing his publications, speeches, and public policy initiatives, the volume offers telling insights into the critical roles of universities, public intellectuals, and diplomats in working together to find solutions to domestic and international problems through public and scholarly engagement. In this way, the volume highlights the very connections that Bunche exhibited as an academic, intellectual, and diplomat."--Jacket.
Ralph Bunche: a personal Memoir / John Hope Franklin -- Framing the conceptual landscape / Beverly Lindsay -- pt. 1. Origins and manifestations of public intellectualism. Rethinking the early life / Ben Keppel -- Responsibilities of the public intellectual / Jonathan Scott Halloway -- A world view of race revisited / Charles P. Henry -- Political science educational contributions: integrating theory and practice / Hanes Walton Jr. -- pt. 2. Educational venues and public intellectualism and diplomacy. Educational and diplomatic influences at public research universities / Beverly Lindsay -- Intellectual and diplomatic imprints at liberal arts colleges / Beverly Lindsay -- An early vision of education: applying knowledge to social engagement / Lorenzo DuBois Baber and Beverly Lindsay -- pt. 3. Diplomats articulating diplomacy. Diplomat in pursuit of the international interest / Edwin Smith -- An international legacy: the Middle East, Congo, and United Nations peacekeeping / Princeton N. Lyman -- pt. 4. Contemporary and future critical international inquiries and models. Complexities abound: paradigms for future public intellectuals and diplomats / Beverly Lindsay.
Includes bibliographical references (p. [173]-187) and index.
JSTOR
Keywords: Bunche, Ralph J. -- 1904-1971.; Bunche, Ralph J. -- 1904-1971 -- Influence; United Nations -- Biography; Bunche, Ralph J. -- 1904-1971; United Nations; Bunche, Ralph J; Statesmen -- United States -- Biography; Intellectuals -- United States -- Biography; Nobel Prize winners -- Biography; African Americans -- Biography; International relations -- History -- 20th century; United States -- Intellectual life -- 20th century; Hommes d'État -- États-Unis -- Biographies; Intellectuels -- États-Unis -- Biographies; Noirs américains -- Biographies; États-Unis -- Vie intellectuelle -- 20e siècle.; BIOGRAPHY & AUTOBIOGRAPHY / General; African Americans; Influence (Literary, artistic, etc.); Intellectual life; Intellectuals; International relations; Nobel Prize winners; Statesmen; United States; Nobelpristagare -- biografi; 1900-1999; Biographies; History; Biographies; Biographies